Enhanced Lesion‐to‐Bubble Ratio on Ultrasonic Nakagami Imaging for Monitoring of High‐Intensity Focused Ultrasound. (1st June 2014) - Zhang, Siyuan; Li, Chong; Zhou, Fanyu; Wan, Mingxi; Wang, Supin
Abstract : Objectives: This work explored the feasibility of using ultrasonic Nakagami imaging to enhance the contrast between thermal lesions and bubbles induced by high‐intensity focused ultrasound (US) in a transparent tissue‐mimicking phantom at different acoustic power levels. Methods: The term "lesion‐to‐bubble ratio" was proposed and defined as the ratio of the scattered power from the thermal lesion to the scattered power from the bubbles calculated in the various monitoring of images for high‐intensity focused US. Two‐dimensional radiofrequency data backscattered from the exposed region were captured by a modified diagnostic US scanner to estimate the Nakagami statistical parameter, m, and reconstruct the ultrasonic B‐mode images and Nakagami parameter images. The dynamic changes in the lesion‐to‐bubble ratio over the US exposure procedure were calculated simultaneously and compared among video photos, B‐mode images, and Nakagami images for monitoring of high‐intensity focused US. Results: After a small thermal lesion was induced by high‐intensity focused US in the phantom, the lesion‐to‐bubble ratio values corresponding to the video photo, B‐mode image, and Nakagami image were 5.3, 1, and 9.8 dB, respectively. When a large thermal lesion appeared in the phantom, the ratio values increased to 7.2, 3, and 14 dB. During US exposure, the ratio values calculated for the video photo, B‐mode image, and Nakagami image began to increase gradually and rose to peak values of 8.3, 2.9, and 14.8 dB at the end of the US exposure. Conclusions: This preliminary study on a tissue‐mimicking phantom suggests that Nakagami imaging may have a potential use in enhancing the lesion‐to‐bubble ratio for monitoring high‐intensity focused US. Further studies in vivo and in vitro will be needed to evaluate the potential applications for high‐intensity focused US.